2017
DOI: 10.1038/s41598-017-11736-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the Middle East respiratory syndrome coronavirus 4a protein and its dsRNA binding mechanism

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) has evolved to navigate through the sophisticated network of a host's immune system. The immune evasion mechanism including type 1 interferon and protein kinase R-mediated antiviral stress responses has been recently attributed to the involvement of MERS-CoV protein 4a (p4a) that masks the viral dsRNA. However, the structural mechanism of how p4a recognizes and establishes contacts with dsRNA is not well explained. In this study, we report a dynamic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 73 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…which shows the high structural similarity. 4,8,9 Experimental binding affinity measurements using Surface Plasmon Resonance (SPR) have shown that nCOV-3 fold higher affinity than SARS-COV binding to ACE2. 7 Based on the sequence similarity between RBD of nCOV-2019 and SARS-COV and also the tight binding between RBD of nCOV-2019 and ACE2, it is most probable that nCOV-2019 uses this receptor on human cells to gain entry into the body.…”
Section: Introductionmentioning
confidence: 99%
“…which shows the high structural similarity. 4,8,9 Experimental binding affinity measurements using Surface Plasmon Resonance (SPR) have shown that nCOV-3 fold higher affinity than SARS-COV binding to ACE2. 7 Based on the sequence similarity between RBD of nCOV-2019 and SARS-COV and also the tight binding between RBD of nCOV-2019 and ACE2, it is most probable that nCOV-2019 uses this receptor on human cells to gain entry into the body.…”
Section: Introductionmentioning
confidence: 99%
“…These data, along with the genetic link observed in yeast, suggest that ORF4a and SIRT1 may have a functional connection without direct binding and that there is an additional node of regulation between the two proteins, which is under investigation. This work adds SIRT1 to the list of host factors that mediate MERS-CoV replication such as stress granule formation and host innate immune machinery ( 9 12 ). The magnitude of inhibition when those factors are affected is ∼1 log, demonstrating that, as seen in SIRT1, host machinery interacts with various virus replication steps to potentially hinder replication.…”
Section: Discussionmentioning
confidence: 99%
“…One such protein, produced by MERS-CoV, is ORF4a. This accessory protein has been shown in vitro to bind double-stranded RNA and to disrupt the innate immune sensing pathways of RIG-I and MDA5 to suppress the interferon response ( 7 9 ). Additionally, ORF4a has been found to inhibit the PKR and stress granule response in cells ( 10 12 ), further interfering with cellular function to promote viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…66 ORF4a's protein can mask viral dsRNA to play a role in immune evasion, including type 1 IFN and protein kinase R-mediated antiviral stress responses. 67 MERS-CoV NSP13 is a full-length coronavirus helicase that contains multiple domains, including an N-terminal Cys/His rich domain with three zinc atoms, a beta-barrel domain and a C-terminal superfamily (SF) 1 helicase (SF1) core with two RecA-like subdomains. This protein might interfere with the nonsensemediated mRNA decay pathway to avoid degradation of viral RNA.…”
Section: Epidemiological Analysis and Symptoms Of Sars Mers And Cormentioning
confidence: 99%